Pengetahuan Ibu Tentang Gizi Berhubungan Dengan Kejadian Stunting Pada Balita Umur 24-36 Bulan - Palupi, Fitria Hayu; Renowening, Yuniars; Mahmudah, Himmatunnisak (Jurnal Kesehatan Mahardika, 2023)
The problem of stunting in the city of Bandung is a priority, because the incidence of stunting in the city of Bandung is one of the highest in West Java, which is 6.63%. Stunting can be prevented by increasing maternal knowledge about stunting prevention. The purpose of this study was to analyze the relationship between maternal knowledge about nutrition and the incidence of stunting in toddlers aged 24-36 months. This research uses quantitative methods and cross-sectional design. The population of this study was mothers who had toddlers aged 24-36 months who lived in the working area of the Cipadung Health Center. The number of samples in this study was 108 respondents. Sampling uses a simple random sample technique. The statistical test used in this study is the chi square test. There are 32.4% of toddlers who are stunted, and most mothers have a high knowledge of nutrition at 62%. There is a relationship between maternal knowledge about nutrition and the incidence of stunting (p=0.027, and OR=2.7). Mothers who have low knowledge of nutrition are 2.7 times more likely to have stunted children compared to mothers who have high knowledge of nutrition